Analisis Pengaruh Pengawasan Dan Keterampilan Kerja Serta Gaji Terhadap Kinerja Karyawan Pada Bengkel Cv. Teguh Harapan Di Kabupaten Berau - Rahman Rahman (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The aims of this study were to determine the effect of supervision, work skills, and salaries jointly and partially had a significant effect on employee performance at CV. Teguh Harapan in Berau Regency and analyzing the dominant influence among the variables of supervision, work skills, and salary which have a dominant effect on employee performance at CV. Teguh Harapan in Berau Regency. This type of research was a quantitative study based on hypothesis testing. The population and sample of this study were all employees of CV. Teguh Harapan who had worked for more than 1 year were 100 employees. The data analysis method used multiple linear regressions. The results showed that supervision does not have a significant effect on employee performance. Work Skills already had significant influence on employee performance. Investment had a significant influence on employee performance at CV. Teguh Harapan Workshop in Berau Regency. Kata Kunci: Gaji, Ketrampilan Kerja, Kinerja, Karyawan dan Pengawasan.